Weather Conditions in Relation to Crimes Committed in Pagadian City - Mangubat, Junry M.; Pallega, Rowell B.; Aranjuez, Nancy E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to determine the relationship between weather conditions as to wet and dry as recorded in the Department of Science and Technology (DOST) – Philippine Atmospheric, Geophysical and Astronomical Services Administration (PAGASA) Weather Forecast Station and the crimes committed in Pagadian City in calendar years 2014-2018. Weather conditions as to wet and dry were correlated to crimes against person and property that was committed in Pagadain City. It employed a quantitative descriptive correlational method of research using the data of crime occurrences recorded in the Philippine National Police Pagadian City Station and the rainfall data from Department of Science and Technology (DOST) – Philippine Atmospheric, Geophysical and Astronomical Services Administration (PAGASA) Weather Forecast Station in the city statistically treated using frequency count, mean, paired sample t-test, and chi-square test. Findings of the study revealed that physical injuries were profiled the highest in crimes against persons, followed by murder, homicide, and rape. At the same time, theft cases were dominantly registered for crimes against properties, followed by robbery, carnapping, and cattle rustling. The average distribution of murder, homicide, and physical injuries during the wet season outnumbered the cases during the dry season, except for rape cases that were higher during the dry season. Likewise, robbery, theft, carnapping, and cattle rustling were higher during the wet season than the dry season. The average distribution differences of crimes committed between the wet and the dry seasons tested at a 0.05 level of significance were not significant. The relationship between crimes against persons and the weather conditions was not significant. The relationship between crimes against properties and the weather conditions was also not significant. Moreover, crimes against persons and properties in the city do not depend on weather conditions. Murder, homicide, physical injuries, rape, robbery, theft, carnapping, cattle rustling, and the like could happen in the city regardless of whether it is wet or dry weather conditions, and there is a need to implement the crime prevention programs designed by the researcher.